Prediagnostic Serum Concentrations of Organochlorine Compounds and Risk of Testicular Germ Cell Tumors - Purdue, Mark P. (National Institute of Environmental Health Sciences, 2009)
BACKGROUND: Recent findings suggest that exposure to organochlorine (OC) compounds, chlordanes and p,p′-dichlorodiphenyldichloroethylene (p,p′-DDE) in particular, may increase the risk of developing testicular germ cell tumors (TGCTs). OBJECTIVE: To further investigate this question, we conducted a nested case–control study of TGCTs within the Norwegian Janus Serum Bank cohort. METHODS: The study was conducted among individuals with serum collected between 1972 and 1978. TGCT cases diagnosed through 1999 (n = 49; 27–62 years of age at diagnosis) were identified through linkage to the Norwegian Cancer Registry. Controls (n =51) were matched to cases on region, blood draw year, and age at blood draw. Measurements of 11 OC insecticide compounds and 34 polychlorinated biphenyl (PCB) congeners were performed using gas chromatography/high-resolution mass spectrometry. Case–control comparisons of lipid-adjusted analyte concentrations were performed using the Wilcoxon signed-rank test. Odds ratios (ORs) and 95% confidence intervals (CIs) for tertiles of analyte concentration were calculated using conditional logistic regression. RESULTS: TGCT cases had elevated concentrations of p,p′-DDE (tertile 3 vs. tertile 1 OR (OR(T3)) 2.2; 95% CI, 0.7–6.5; p(Wilcoxon) = 0.07), oxychlordane (OR(T3) 3.2; 95% CI, 0.6–16.8; p(Wilcoxon) = 0.05), trans-nonachlor (OR(T3) 2.6; 95% CI, 0.7–8.9; p(Wilcoxon) = 0.07), and total chlordanes (OR(T3) 2.0; 95% CI, 0.6–7.2; p(Wilcoxon) = 0.048) compared with controls, although no ORs were statistically significant. Seminoma cases had significantly lower concentrations of PCB congeners 44, 49, and 52 and significantly higher concentrations of PCBs 99, 138, 153, 167, 183, and 195. CONCLUSIONS: Our study provides additional but qualified evidence supporting an association between exposures to p,p′-DDE and chlordane compounds, and possibly some PCB congeners, and TGCT risk.